Algorithmic aspects of cloud computing : third International Workshop, ALGOCLOUD 2017, Vienna, Austria, September 5, 2017, Revised selected papers /: third International Workshop, ALGOCLOUD 2017, Vienna, Austria, September 5, 2017, Revised selected papers. (2018) - Unknown
No abstract available